Ethnozoology of bushmeat - Romain Duda; Sandrine Gallois; Victoria Reyes-García (Revue d'ethnoécologie)
In the Congo Basin, food is an everyday concern and its acquisition and transformation often structure many of the activities of a human group. While agriculture provides the main source of calories, meat of wild animals, commonly referred to as bushmeat, represents the main source of protein for local people in the region and plays an important role in terms of dietary diversity and health. However, the increase of bushmeat consumption in towns and more efficient hunting practices have pushed the harvest of wild animals to unsustainable levels, generating a “bushmeat crisis”. The growing demand for bushmeat has created strong pressures and a lure of profit pushing the hunters of southern Cameroon to sell (illegally) their harvest. A dynamic that might affect both local diets and the modalities of relations between humans and animals. Therefore, this paper aims to describe the importance of wild meat for the Baka, an ethnolinguistic group of Southeastern Cameroun, traditionally hunter-gatherers. It analyses the place of the animal in the Baka daily life through its contribution in dietary, symbolic and economic terms. The paper combines a qualitative ethnography with individual-level data on food diversity intake and meat selling, and describes different aspects related to meat sharing and consumption.